Is there a new state in Latin America?: Lessons after COVID-19 - Santarcangelo, Juan Eduardo (2022)
COVID-19 was declared a pandemic in March 2020 and struck a global economy in a situation of enormous fragility (the lowest growth rate since the international financial crisis of 2008). This situation was extremely severe in the case of Latin America, which was not only the region with the worst performance in the global south in 2019, but also where neoliberalism has generated one of the most profound transformations both in the structure of the state and in the direction of its public policies. The aim of this paper is to review and compare the public policies implemented by the different Latin American governments at the beginning of the pandemic, to study how well local and national governments were prepared for it in terms of capacity, to analyse the effectiveness of the public policies applied and to derive some lessons that we should learn for the future. The paper shows that the pandemic brought to light the structural deficiencies generated by decades of neoliberalism in the region and demonstrates that only through a profound transformation in the state and its capacities will the peripheral countries be prepared to face similar challenges.